Total and size-resolved particle number and black carbon concentrations near an industrial area. (December 2015) - Keuken, M.P.; Moerman, M.; Zandveld, P.; Henzing, J.S.
Abstract: Total and size-resolved particle number and black carbon concentrations were investigated in urban areas of the city of Rotterdam (the Netherlands) situated near an industrial area. Several monitoring campaigns were conducted in the period 2011–2014 at three local locations and at a regional background site. Black carbon levels showed minor elevation due to industrial emissions. In contrast, particle number concentrations (PNC) increased during periods with wind directions from the industrial area, by 1000 to 23, 000 particles per cm 3 depending on the distance to the area from 1 to 40 km. The size distribution of elevated PNC was characterized by two modes: 10–20 nm (nucleation particles) and 20–100 nm (Aitken particles). Five dominant industrial sources were identified and used as input for dispersion modelling of PN in 2012. The results showed that in Rotterdam about 70, 000 addresses were exposed to an additional annual PNC of 5000–10, 000 particles per cm 3 and about 55, 000 addresses to additional PNC of 10, 000–20, 000 particles per cm 3 for 39% of the time. More measurements of PNC up- and downwind of the industrial area are recommended to identify more accurately the PN emission sources and to validate the dispersion modelling. Highlights: Ultrafine particles are a factor 3 elevated 5 km downwind industrial area. The size-distribution of these particles is dominated by particles of 10–50 nm. 70, 000 addresses exposed to annual average additional 5–10, 000 #/cm 3 .